Cdc45-induced loading of human RPA onto single-stranded DNA. Issue 6 (18th January 2017) - Szambowska, Anna; Tessmer, Ingrid; Prus, Piotr; Schlott, Bernhard; Pospiech, Helmut; Grosse, Frank
Abstract: Cell division cycle protein 45 (Cdc45) is an essential component of the eukaryotic replicative DNA helicase. We found that human Cdc45 forms a complex with the single-stranded DNA (ssDNA) binding protein RPA. Moreover, it actively loads RPA onto nascent ssDNA. Pull-down assays and surface plasmon resonance studies revealed that Cdc45-bound RPA complexed with ssDNA in the 8–10 nucleotide binding mode, but dissociated when RPA covered a 30-mer. Real-time analysis of RPA-ssDNA binding demonstrated that Cdc45 catalytically loaded RPA onto ssDNA. This placement reaction required physical contacts of Cdc45 with the RPA70A subdomain. Our results imply that Cdc45 controlled stabilization of the 8-nt RPA binding mode, the subsequent RPA transition into 30-mer mode and facilitated an ordered binding to ssDNA. We propose that a Cdc45-mediated loading guarantees a seamless deposition of RPA on newly emerging ssDNA at the nascent replication fork.